Depositional Environments and Sediments in the Coastal Zone of Prince Edward Island, Canada - Bartlett, Grant (Atlantic Geology, 1977)
Prince Edward Island has an area of 5700 km2 , with a length of approximately 217 km and an average width of 27 km. Numerous coastal indentations account for a total coastline of over 1,770 km. Shallow bays and estuaries cut deeply into the landmass and nearly dissect it in several places. Man has established his major communities, industries, and recreational activities along the coastline and is being drawn there in increasing numbers, thereby placing undue pressure on the vevy environmental qualities which formed the original attraction. The estuaries produce large quantities of organic materials, and act as sediment traps and reservoirs for nutrients and chemicals. The processes of trapping, concentrating, producing and recycling sediments are of first order importance. Sediments in the estuaries and lagoons range from clay to coarse sand and gravel. They are contributed by marginal, internal and external sources. Sediment accumulation averages 0.4 cm/year. Fluvial waters transport and contribute the majority of the sediments to these environments. Tidal flow contributes to the resuspension and redistribution of river-borne sediments. Agglomeration, flocculation and deflocculation occurring in these estuaries have important affects on siltation and pollutant concentration. Organic constituents in the sediments are derived from pelagic, epi- and infaunas. The inorganic constituents are derived from a variety of sources. Concentrations of suspended particulate matter decrease from about 180 mg/l in upper estuaries to less than 3 mg/l in the lower estuary-lagoon complex. The organic matter content is highest (-3 to 5%) in fine-grained sediments. Heavy metals such as Cu, Pb and In are strongly associated with organic matter. River flow and the flood and ebb of tidal currents are the most obvious water motions in these environments. However, strong winds cause turbulence in shallow (< 5 m) waters. This turbulence initiates resuspension of previously deposited organic and inorganic materials. Depending upon the relative directions of wind and tide, winds may cause an increase or decrease in surface current velocities.